A Hermeneutical Study of Mass Media Cartoons in The Political Year of 2024 - I Wayan Nuriarta; Ida Ayu Dwita Krisna Ari (Institute of Research and Community Outreach - Petra Christian University, 2026)
Mass media cartoons are works of visual communication that have the 'task' of conveying opinions or criticism of socio-political discourse with a touch of humor. This research aims to describe the visual structure of political cartoons and the role of humour in these cartoons in conveying opinions in mass media. The research design utilises a qualitative approach, with data sourced from the KOMPAS newspaper cartoons by cartoonist Thomdean, published on February 14 and April 24, 2024, and weekly cartoons from TEMPO magazine by Yuyun Nurrachman, from the issues of January 15-21 and January 22-28, 2024. Theories applied in this research include visual communication design, humour theory, and hermeneutics. The results show that the political cartoons in KOMPAS and TEMPO are conveyed through a single-panel storytelling format and utilise humour to communicate political messages. This political cartoon focuses on the general election with an explicit narrative as a representation of visual power. This humour is evident in the visual elements and the written text. The intended message becomes more acceptable to diverse audiences, including those critiqued for using this political humour.